Papers read at the Conference on the problems of the rural church: held in Boston March 13 and 14, 1911 (Cosmos Press, 1911)
Wilson, W.H. The church for the working farmer.--Rowe, H.K. Some statistics of church attendance and church work in rural New England.--Pardee, J.N. The awakening of the theological schools.--Parker, E.M. An ideal of country church settlement work.--Sprague, R.J. The rural church and the beautification of the country.--Cutler, M.L. One solution of the problem of the country church.--Benson, O.H. Education for rural life.